Dabrafenib and trametinib versus dabrafenib and placebo for Val600 BRAF-mutant melanoma: a multicentre, double-blind, phase 3 randomised controlled trial. Issue 9992 (1st August 2015) - Long, Georgina V; Stroyakovskiy, Daniil; Gogas, Helen; Levchenko, Evgeny; de Braud, Filippo; Larkin, James; Garbe, Claus; Jouary, Thomas; Hauschild, Axel; Grob, Jean-Jacques; Chiarion-Sileni, Vanna; Lebbe, Celeste; et al.
Summary: Background: Previously, a study of ours showed that the combination of dabrafenib and trametinib improves progression-free survival compared with dabrafenib and placebo in patients with BRAF Val600Lys/Glu mutation-positive metastatic melanoma. The study was continued to assess the secondary endpoint of overall survival, which we report in this Article. Methods: We did this double-blind phase 3 study at 113 sites in 14 countries. We enrolled previously untreated patients with BRAF Val600Glu or Val600Lys mutation-positive unresectable stage IIIC or stage IV melanoma. Participants were computer-randomised (1:1) to receive a combination of dabrafenib (150 mg orally twice daily) and trametinib (2 mg orally once daily), or dabrafenib and placebo. The primary endpoint was progression-free survival and overall survival was a secondary endpoint. This study is registered with ClinicalTrials.gov, number NCT01584648 . Findings: Between May 4, 2012, and Nov 30, 2012, we screened 947 patients for eligibility, of whom 423 were randomly assigned to receive dabrafenib and trametinib (n=211) or dabrafenib only (n=212). The final data cutoff was Jan 12, 2015, at which time 222 patients had died. Median overall survival was 25·1 months (95% CI 19·2–not reached) in the dabrafenib and trametinib group versus 18·7 months (15·2–23·7) in the dabrafenib only group (hazard ratio [HR] 0·71, 95% CI 0·55–0·92; p=0·0107). Overall survival was 74% at 1 year and 51% at 2 years in the dabrafenib and trametinib group versus 68% and 42%, respectively, in the dabrafenib only group. Based on 301 events, median progression-free survival was 11·0 months (95% CI 8·0–13·9) in the dabrafenib and trametinib group and 8·8 months (5·9–9·3) in the dabrafenib only group (HR 0·67, 95% CI 0·53–0·84; p=0·0004; unadjusted for multiple testing). Treatment-related adverse events occurred in 181 (87%) of 209 patients in the dabrafenib and trametinib group and 189 (90%) of 211 patients in the dabrafenib only group; the most common was pyrexia (108 patients, 52%) in the dabrafenib and trametinib group, and hyperkeratosis (70 patients, 33%) in the dabrafenib only group. Grade 3 or 4 adverse events occurred in 67 (32%) patients in the dabrafenib and trametinib group and 66 (31%) patients in the dabrafenib only group. Interpretation: The improvement in overall survival establishes the combination of dabrafenib and trametinib as the standard targeted treatment for BRAF Val600 mutation-positive melanoma. Studies assessing dabrafenib and trametinib in combination with immunotherapies are ongoing. Funding: GlaxoSmithKline.